Utilization of Flour Maggot (Hermetia Illuncens L) as A Substitute Fish Flour for Growth of Selais Fish (Ompok Hyphoptalmus) Seed - Aryani, Netti; ', Marno; ', Adelina (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2016)
This research aims to find out the effect of utilization of flour maggot as asubstitute fish flour in feed to increase the growth of selais fish (Ompokhyphoptalmus)seed. This research used Completely Randomized Design (CRD)methodwith one factor, five-stage treatment and 3 replicates.Treatment with thesubstitution of flour maggot: fish flour, control P0(0%:100%), P1 (25%:75%), P2(50%:50), P3 (75%:25%), P4 (100%:0%). The protein content 25,04 – 29,43%.The result showed the best treatment at P0 treatment (0%:100%) with a spesificgrowth rate 1,69%, the rate of feed efficiency16,59%,feed digestibility 65,40%and the survival 98,33%.Keyword: (Ompok hyphoptalmus), flour maggot, growth, feed